Muziejų leidybinė veikla Estijoje: leidiniai ir procesai (2011 ‒ 2015 m.) - Möldre, Aile; Tuuling, Liivi (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian] The article introduces the study of museum publishing in Estonia in 2011‒2015 that aims at establishing the production trends and the characteristic features of the publishing process. Production data was gathered from the Estonian national bibliography database, information about the organisation of the publishing process was collected via interviews and a survey. The data collection identified 467 non-periodical and7 periodical publications, including mainly printed books (catalogues, museum guides, conference collections, etc.), dominated by scholarly content and art books. E-books were mainly represented by relatively few publications of educational materials and scholarly texts, issued both on paper and in pdf format. The first stages of the publishing process (writing and editing) as well as distribution are usually done in-house in all the studied museums. The larger museum publishers also handle the design and layout themselves whereas the smaller museums use outsourcing. Translation and printing is usually outsourced by all museums. Making their future plans, the museums consider wider use of print on demand as well as strengthening of marketing activities.